Development of a signal integrity analysis tool based on transmission line theory - Soe Moe Kyaw. (2008)
This project is developed for the purpose of predicting signal reflection due to the mismatches of the signal line at the load and source ends and the prediction of crosstalk response for a pair of coupled microstrip lines by using the MATLAB. The simulation results have been validated with a reference paper for signal reflection and with measurement results for crosstalk response.